Surgical treatment of melanoma of the iris and ciliary body - Romanowska, Bożena; Żygulska-Mach, Helena; Bryk, Janusz; Orłowska-Heitzman, Jolanta; Sajak-Hydzik, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 1999)
Evaluation of surgical treatment of melanoma of the iris and ciliary body. 50 patients with tumor in the region of the iris and ciliary body at the age of 16-69 years were operated. Among them there were 32 women and 18 men. Tumors of the iris were found in 31 patients, and tumors of the iris and ciliary body in 19 patients. The tumors of the iris were excised through a limbal incision, while the tumors of the ciliary body were excised after preparation of the scleral flap. In 6 cases additional irradiation with 106 Ru plaques was performed. In 1 case the plaque with 60 Co was used in the dose of 60 Gy at the depths of 3 mm. Follow-up time was 6 months to 3 years. In order to evaluate the influence of the methods of the treatment on the corneal epithelium, in 16 patients a specular microscope examination was carried out. In 11 patients the influence of the treatment on autofluorescence of the lens was studied, using fluorophotometer. Histopathological examination of the excised tumors revealed in all cases A and B type of spindle cell malignant melanoma, except in three cases of mixed cell melanoma. No serious complication was observed as a result of surgery. Disturbances in the density of corneal epithelium due to 106 Ru irradiation was observed in 2 cases. Increase of autofluorescence of the lens was observed in 4 patients with the initial cataract.